2011
DOI: 10.1161/strokeaha.110.609693
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Size

Abstract: Background and Purpose-We hypothesize that in acute middle cerebral artery stroke, thrombus lengths measured in thin-slice nonenhanced CT images define a limit beyond which systemic thrombolysis will fail to recanalize occluded arteries. Methods-In 138 patients who presented with acute middle cerebral artery stroke and who were treated with intravenous thrombolysis (IVT), we measured lengths of thrombotic clots depicted as arterial hyperdensities in admission nonenhanced CT images with 2.5-mm slice width. Vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
229
4
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(245 citation statements)
references
References 12 publications
5
229
4
7
Order By: Relevance
“…One study suggested that HMCAS disappearance post-thrombolysis occurs only in hyperdense arteries with a thrombus length of 8 mm or less, 7 whereas 83% of those we observed in whom HMCAS disappeared had a HMCAS length greater than 8 mm. Another study of 41 thrombolysed patients with HMCAS also suggested that HMCAS disappearance is length dependent, occurring in 86% with lengths < 10mm, 38% if 10-20 mm, and in no cases > 20 mm.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…One study suggested that HMCAS disappearance post-thrombolysis occurs only in hyperdense arteries with a thrombus length of 8 mm or less, 7 whereas 83% of those we observed in whom HMCAS disappeared had a HMCAS length greater than 8 mm. Another study of 41 thrombolysed patients with HMCAS also suggested that HMCAS disappearance is length dependent, occurring in 86% with lengths < 10mm, 38% if 10-20 mm, and in no cases > 20 mm.…”
Section: Discussioncontrasting
confidence: 55%
“…Disappearance of the HMCAS is more likely following intravenous thrombolysis 3 and is associated with improved outcome. 4 Recent studies suggest that occlusion site, 5 clot length, 6,7 and thrombus Hounsfield Unit (HU) quantification 1,8,9 are all candidates to predict vessel recanalisation after intravenous thrombolysis. It has also been suggested that HMCAS due to cardio-embolism has higher vessel attenuation and is more likely to recanalise post-thrombolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous tPA has been recently shown to be safe in a subset of stroke patients to a maximum of 4.5 h from symptom onset with an 8% benefit in increasing the probability of good outcomes [9,10]. Patients with large vessel occlusions [11,12] and those with large thrombus burden (i.e., thrombi longer than 8 mm) [13], and those with more severe strokes respond less well to IV thrombolysis [14]. For these patients, IAT may be considered as an alternative to IV thrombolysis, although currently IV tPA is the only validated approach and its use is recommended to a maximum of 4.5 h from stroke onset [10].…”
Section: Indicationsmentioning
confidence: 99%
“…More specifically, thrombi longer than 8 mm measured in thin‐slice nonenhanced brain CT scans were found to be almost impossible (<1%) to dissolve with IVTPA in a recent single‐center study (Riedel et al. 2011). In short, the benefit for stroke patients receiving IVTPA is hampered by a short window of opportunity, many exclusion criteria, and most importantly, by only partial efficacy in achieving complete and lasting artery recanalization especially in cases with high clot burden.…”
Section: Introductionmentioning
confidence: 99%